2008
DOI: 10.31729/jnma.153
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Primary Intraocular Lens Insertion in Unilateral Childhood Traumatic Cataract

Abstract: This study analyzes the results of cataract surgery with primary intraocular lens implantation inunilateral childhood traumatic cataract following penetrating trauma and its long term follow up.It is a hospital based study of 114 children (age 3-10 years) with unilateral traumatic cataract whounderwent extracapsular cataract extraction/ lens aspiration with implantation of posterior chamberintraocular lens (IOL). Primary posterior capsulotomy (PPC) was performed in 57 eyes and the rest57 were without PPC (NPPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…In our study soft cataract was noticed in 22.5% which is consistent with the study of Shah MA et al in their study showed 59.9% patients had white soft cataract with ruptured anterior capsule followed by 26.6% had total cataract [22]. In our study more than half of patients had pre-treatment best corrected visual acuity of light perception only which is consistent with study of Ahmed N et al [24] where half of patients had visual acuity of hand movement and with study of Kumar S et al [25] where maximum patient had visual acuity of light perception only. In our study, Corneal tear was most common associated ocular damage followed by uveitis, lens matter in anterior chamber.…”
Section: Discussionsupporting
confidence: 92%
“…In our study soft cataract was noticed in 22.5% which is consistent with the study of Shah MA et al in their study showed 59.9% patients had white soft cataract with ruptured anterior capsule followed by 26.6% had total cataract [22]. In our study more than half of patients had pre-treatment best corrected visual acuity of light perception only which is consistent with study of Ahmed N et al [24] where half of patients had visual acuity of hand movement and with study of Kumar S et al [25] where maximum patient had visual acuity of light perception only. In our study, Corneal tear was most common associated ocular damage followed by uveitis, lens matter in anterior chamber.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies document visual outcomes in children with traumatic cataract. Shah et al 4 report that 56% of patients obtained a CDVA of better than 20/60, Krishnamachary et al 12 found a CDVA of better than 20/60 in 74% of cases, and Kumar et al 13 of better than 6/18 in 50% of cases. Staffieri et al 14 report a CDVA of better than better than 0.7 in 27% of cases.…”
Section: Discussionmentioning
confidence: 95%
“…A similar procedure was performed for treatment of traumatic cataracts by and Kumar et al . [ 16 ] and Rastogi et al . [ 17 ] They reported similar results, but only in pediatric subjects; furthermore, no control group was included.…”
Section: Discussionmentioning
confidence: 99%